2016
DOI: 10.1039/c6ra14789e
|View full text |Cite
|
Sign up to set email alerts
|

Production of liquid hydrocarbon fuels with 3-pentanone and platform molecules derived from lignocellulose

Abstract: Diesel or jet fuel range C 10 -C 17 branched and cyclic alkanes were produced by reaction of 3-pentanone derived from lactic acid with bio-based aldehydes through aldol condensation followed by hydrodeoxygenation. DBU (1,8-diazabicycloundec-7-ene) was identified as an efficient catalyst for the aldol reaction of 3-pentanone with furan based aldehydes, and the selectivity of single or double aldol condensation product could be easily controlled by adjusting the reaction temperature. For the reaction with aromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…This process requires synergistic catalysis between the hydrogenation catalyst and solid acid. Encouraged by our previous work, [45][46][47] we found that the commercial catalyst Pd/C added zeolite (H-beta) had the best selectivity for alkanes. During this experiment, 5% equivalent Pd with 0.5 g H-beta (Si/ Al ¼ 40) to 5 mmol C-C coupling products was used as the catalyst and reacted at 473 K, and water as the solvent and 3 MPa hydrogen pressure were required simultaneously.…”
Section: Hydrodeoxygenation Of C-c Coupling Reaction Productmentioning
confidence: 81%
See 2 more Smart Citations
“…This process requires synergistic catalysis between the hydrogenation catalyst and solid acid. Encouraged by our previous work, [45][46][47] we found that the commercial catalyst Pd/C added zeolite (H-beta) had the best selectivity for alkanes. During this experiment, 5% equivalent Pd with 0.5 g H-beta (Si/ Al ¼ 40) to 5 mmol C-C coupling products was used as the catalyst and reacted at 473 K, and water as the solvent and 3 MPa hydrogen pressure were required simultaneously.…”
Section: Hydrodeoxygenation Of C-c Coupling Reaction Productmentioning
confidence: 81%
“…CPO and CPL are versatile chemical intermediates that are applied in various elds of daily life. Inspired by our previous work, [45][46][47] cyclopentanone can be used as a substrate to synthesize diesel range fuels due to its carbonyl group. This process consists of two steps.…”
Section: Hydrodeoxygenation Of C-c Coupling Reaction Productmentioning
confidence: 99%
See 1 more Smart Citation
“…[175,176] EAOAc, was prepared from acetic acid and ethanolamine (a bio-based substrate from cellulose), and displayed the highest activity of the ionic liquids investigated. [177] According to literature reports, [178,179] the hydroxyl group in EAOAc promoted hydrogen bonding between the reactants and catalysts, enhancing the condensation reaction. Free ethanolamine catalyzed the reaction, but higher activity was obtained when the ionic liquid was used.…”
Section: Perhydrofluorene Fuelsmentioning
confidence: 99%
“…20 Furthermore, methyl isobutyl ketone, 2-pentanone, 2-heptanone and 3-pentanone were successively applied to the aldol condensation with furfural, generating linear or singly branched alkanes aer the later hydrogenation/hydrodeoxygenation. [21][22][23][24] Aldol condensation plays an important role in this fuel synthesis strategy, by which the carbon-chain length of platform molecules can increase. In our view, the choice of the second reactant in the furfural aldol condensation is a crucial step, which almost determines the structure of nal products and fuel quality.…”
Section: Introductionmentioning
confidence: 99%